Pasture resilience towards landscape changes: assessing pastures quality in the context of land-use and land-cover changes in Romania - Ana-Maria CALOTA; Ieanaa PATRU-STUPARIU (European Journal of Geography)
The current global context (the expansion of urban concentration, the need to produce green energies, the aging of rural population) and often, the volatile legislative framework create opportunities for irreversible landscape and, implicitly environmental changes. Pastures are under continuous pressure due to the expansion of built-up areas. The expansion of several infrastructures or the refurbishment of the existing ones, decreases the quality of the natural and semi-natural ecosystems. The aim of the current paper consists in identifying which is the impact of land use change over the quality of pastures. The results presented in this paper emphasize that the occurrence of different land use and land cover changes, disturbs the quality of pastures in various ways, depending on the new land use and land cover developed in these primary ecosystems. One of the major outcomes of the study underlines that the continuous decrease of pastures’ surface is a dynamic process that in an indirect way affects the quality of life within society. In this case, a diachronic analysis of the evolution of pastoral areas (by eloquent case studies), as well as a current assessment of their support capacity are, in addition to the existing studies, creating an overall picture that is scientifically valid in future efforts of territorial and zonal planning.